Development of polarization modulator using MXene thin film - Zian Cheak Tiu; Sin Jin Tan; N. Yusoff; Harith Ahmad (Scientific Reports, 2022)
Abstract In this work, polarization modulator utilizing MXene material, namely Nb2C is demonstrated. S band signal is injected into Nb2C thin film and is modulated by 1400 nm laser diode. A total of 39.81° of polarization rotation is attained when the pump power is increased to 223 mW. The rotation of light is due to thermo-optic effect. The efficiency of polarization modulator is calculated at 0.1974°/mW.